Asuransi Dan Investasi Dalam Islam - Alinolas Cubaim Harahap; Aldio Azani Siregar; Taufiqurrahman; Ade Kurnia Sari; Rizqa Amelia (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This study aims to investigate the relationship between insurance and investment from an Islamic perspective, with a focus on adherence to sharia principles. In this context, this study analyzes Islamic principles related to insurance and investment, and their impact on Muslim societies. The research methodology involved a comprehensive literature study and a qualitative analysis of primary and secondary sources relevant to this topic. Various opinions and views from scholars and experts in the field of Islamic finance were also examined and analyzed.